2013
DOI: 10.4172/2329-9517.1000e103
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Surgical Aortic Valve Replacement

Abstract: EditorialOpen AccessThe average survival rate was 3 years after the onset of angina pectoris in patients with severe Aortic Stenosis (AS) [1]. The average survival rate after the onset of syncope in patients with severe AS was 3 years [1]. The average survival rate after the onset of heart failure in patients with severe AS was 1.5 to 2 years [1]. Patients with symptomatic severe valvular AS have a poor prognosis [1][2][3][4]. At the National Institutes of Health, 52% of patients with symptomatic severe valvul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, recent studies have cast doubt on whether the low‐flow state truly portends a poorer prognosis . Studies also appear conflicted on the impact of surgery on these patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have cast doubt on whether the low‐flow state truly portends a poorer prognosis . Studies also appear conflicted on the impact of surgery on these patients …”
Section: Introductionmentioning
confidence: 99%
“…8 Studies also appear conflicted on the impact of surgery on these patients. 9,10 Furthermore, reduced LVEF to <50% is an ACC/AHA class I indication for aortic valve replacement (AVR), even in the absence of symptoms. 11,12 To date, no study has yet examined the deterioration of LVEF over time in patients with low-flow compared to normal-flow severe AS.…”
mentioning
confidence: 99%
“…In addition, some studies have demonstrated that low‐flow severe AS behaved more like moderate AS. Furthermore, the timing and role of surgery in these patients remained unclear . Therefore, the natural history and progression of severe AS in various flow categories remained to be better understood.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced stages of AS warrants surgical aortic valve replacement (AVR) [4]. Despite the aid of echocardiographic parameters allowing for delineation of mild, moderate and severe aortic stenosis, the single prevailing indication for surgical intervention is the severity of symptoms [5].…”
Section: Introductionmentioning
confidence: 99%